Bats - Gibbons, Gail. (New York : Holiday House, 1999)
Describes different kinds of bats, their physical characteristics, habits and behavior, and efforts to protect them.
AD 750
Adult 750
Accelerated Reader AR
Keywords: Bats -- Juvenile literature